Effects of Solids Retention Time on the Anaerobic Membrane Bioreactor with Yttria-Based Ceramic Membrane Treating Domestic Wastewater at Ambient Temperature - Rathmalgodage Thejani Nilusha (Membranes, 2020)
The effects of solid retention times (SRTs) (100 days, 50 days, 25 days) on the performance, microbial community, and membrane fouling of a lab-scale anaerobic yttria-based ceramic membrane bioreactor (AnCMBR) treating synthetic domestic wastewater at ambient temperature (31.2 ± 2.7 °C) were examined. The soluble chemical oxygen demand (SCOD) removal was higher (89.6%) at 25 days SRT compared with 50 days (39.61%) and 100 days (34.3%) SRT. At 100 days SRT, more Bacteroidetes, Firmicutes, and Proteobacteria were present in the microbial community. At 25 days SRT, more Chloroflexi, Synergistetes, and Pastescibacteria emerged, contributing to the stable performance. The SRT of 25 days has resulted in a more stable microbial community compared with 50 days and 100 days SRT. Both bacterial and archaeal community diversities were higher at 25 days SRT, and the specific production of soluble microbial by-products (SMPs) and extracellular polymeric substances (EPSs) were higher at 25 days SRT as well. Consequently, the membrane flux was lower at 25 days SRT with the increased particle size and the enhanced SMPs and EPSs production. Fourier transform infrared spectroscopy analysis (FTIR) and three-dimensional excitation and emission matrix (3D-EEM) analysis showed that protein and SMPs were the major membrane foulants at all SRT stages. In this study, SRT at 25 days was favorable for the stable operation of an AnCMBR treating domestic wastewater at ambient temperature.